Análise espacial da evolução da cobertura e uso da terra no distrito de Santa Flora, Santa Maria, RS - Pereira, Luciano Volenhaupt (2008)
This present work had as objective to spatially analyze the evolution of the covering and usage of the land through the usage of geoprocessing techniques in the district of Santa Flora, Santa Maria, Rio Grande do Sul (RS), in the period of 2000 and 2006. Specifically it was sought to identify, to quantify and to analyze the representative information of the landscape, relating them to the social economical and environmental aspects of the district. In this way, it was used for the accomplishment of the study, Santa Maria's municipal map (1993), the image of the satellite LANDSAT 7 ETM+ (2000) and the image of the satellite CBERS 2 (2006), both of the same time period, implemented by the geoprocessing system SPRING. This system allowed the accomplishment of the classification of the images and in the elaboration of the cartographic elements (cartographic base, hipsometric map, clinographic map and map of the earth usage), associated in parallel to the conference in the field. The classification type was supervised and the images were classified pixel by pixel, and the classifier used was the MAXVER. The thematic classes used for use of land were: forest, farming, field, exposed soil and water. After the stage of image classification, the crossing of the thematic maps was done. With the aid of the LEGAL programming, it was determined the forest evolution, the evolution of the farming field with the following classes: increase, maintenance, decrease, and the areas of permanent preservation in agreement with the current legislation. Among the key findings are referred to the increase area of farming class in 11.008,00 ha between the periods from 2000 to 2006, increasing by more than 100%. Consequently, there was a decline in forest area (6.825,32 ha) in the field (21.291,32 ha) in the period of 2006, due to the expansion of the primary sector, in this case farming. The results enabled know, track and explore the coverage and use of the land through the techniques of geoprocessing, providing subsidies for the different areas. It should be noted that in this study, the agricultural activities are responsible for the changes in coverage and use of the land assigned to socioeconomic policy of the primary sector.